2015
DOI: 10.1063/1.4906174
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic versus kinetic control in self-assembly of zero-, one-, quasi-two-, and two-dimensional metal-organic coordination structures

Abstract: Four types of metal-organic structures exhibiting specific dimensionality were studied using scanning tunneling microscopy and Monte Carlo simulations. The four structures were self-assembled out of specifically designed molecular building blocks via the same coordination motif on an Au(111) surface. We found that the four structures behaved differently in response to thermal annealing treatments: The two-dimensional structure was under thermodynamic control while the structures of lower dimension were under k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…This suggests that the nodes contain more than one metal atom, but probably not more than a dozen: the physical size of clusters much larger than this would not be able to accommodate the observed elongation along the [010] surface direction. Along the [- [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] direction, the BPDCA molecule and the metal cluster are not able to form a structure with a matching lattice periodicity (see Figure 8b). Energetically this complex is more than 2 eV less favorable than the structure along the [010] direction.…”
Section: Co-adsorption Of Bpdca and Fementioning
confidence: 96%
“…This suggests that the nodes contain more than one metal atom, but probably not more than a dozen: the physical size of clusters much larger than this would not be able to accommodate the observed elongation along the [010] surface direction. Along the [- [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] direction, the BPDCA molecule and the metal cluster are not able to form a structure with a matching lattice periodicity (see Figure 8b). Energetically this complex is more than 2 eV less favorable than the structure along the [010] direction.…”
Section: Co-adsorption Of Bpdca and Fementioning
confidence: 96%
“…In recent years, our groups and others have shown that programming organic molecules, through an appropriate geometrical combination of different peripheral recognition moieties, allows the formation of nanostructured surfaces featuring different architectures with various shapes and dimensions. [23][24][25][26][27][28] For example, exploiting the aptitude of pyridyl and cyanophenyl groups to engage in H-bonding, dipole-dipole or metal coordination interactions interactions, [29][30][31][32][33] functional porphyrin derivatives [34][35] featuring programmed geometries could be selectively organized in the presence of metal atoms as supramolecular polymers, 36 discrete macrocycles 37 or arrays with one 38 or two metal atoms. 31 In this context, photoactive polycyclic aromatic hydrocarbons (PAHs) are also of great interest due to their relevance in molecular electronics and photovoltaics.…”
mentioning
confidence: 99%
“…This crystal size dependence on the band-gap and anisotropy absorbance of MIRO 101 can be explained in terms of two alternative orientations that tetrazole ligands adopt in the unit cell during growth, a type of polymorphism that is sensitive to the synthesis conditions. 49,50 Under its first reported synthesis conditions, 46 Zn(3-ptz) 2 (MIRO 101) was obtained in powder form. The x-ray diffraction pattern shows that the asymmetric unit of MIRO 101 exhibits static disorder in which the nitrogen atom of pyridyl group is located in the same crystallographic position of the carbon atom at position 3 in the pyridine, producing two types of pyridil orientations in the unit cell that coexist in a polycrystalline sample.…”
Section: Resultsmentioning
confidence: 99%